Perencanaan Lanskap Kawasan Pura Dalem Mutering Jagat Kesiman - Krisdiandinata, I Kadek Hendra; Asmiwyati, I Gusti Agung Ayu Rai; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap, 2021)
The Landscape Planning of The Area in The Pura Dalem Mutering Jagat Kesiman. The sanctum area is an area around a temple that needs to be kept sacred within a certain radius within the Parisada Hindu Dharma Indonesia Central Decree, concerning Bhisama Kesucian Pura. Pura Dalem Mutering Jagat Kesiman (PDMJK) as Khayangan Tiga temple in Denpasar-Bali has a sacred radius area, namely Apenyengker. Some obstacles have interfered with the activities and sanctity of the temple that will need to be overcome, to be able to create a more sanctum area. The primary objective of the research was to plan the ideal sanctum and also to identify the biophysical and socio-cultural aspects. The method used was the survey method by considering the value of abiotic - biotic (biophysical) and culture (socio-cultural). At the same time, the stages were data inventory, analysis, synthesis, basic concepts, concept development, and planning stages. The data analysis and synthesis were carried out from the socio-cultural and biophysical aspects of qualitative descriptive and quantitative spatial by using the MCDA (multicriteria decision analysis) method. From the research results, there was a steep slope of land into a danger signal which concludes that the area needs to be conserved. The poor spatial planning, especially the temporary stall and parking area, was still unorganized. The spatial planning concept resulted in 3 (three) zones, namely the sacred zone, the conservation buffer zone, and the profane zone. The plan was to use the vegetation concept to vegetate the area with Balinese ceremony plants with conservation value. The idea of circulation was the foundation for the circulation of pedestrians and transportation circulation. The development of the facilities was needed to create new space and support the activities at PDMJK such as park benches, gates, canteen and pedestrians.